Intensive reduction of fuel consumption in the sintering process of double-layered fuel segregation with return fines embedding. (15th January 2023) - Sun, Chengfeng; Ma, Panshuai; Deng, Junyi; Bai, Lingxiao; Liao, Zhehan; Pei, Yuandong; Zhang, Qiaoyu; Xu, Jian
Graphical abstract: Highlights: The return fines embedding technology is proposed to reduce fuel consumption. Return fines are recommended to embed in the lower layer of the sintering bed. The O2 concentration in flue gas is decreased while the gas temperature is increased. The fuel consumption can be reduced by 16% at most via the sintering pot test. The fuel combustion is intensified due to the improved permeability. Abstract: Fuel combustion provides the essential energy required for the iron ore sintering process, this process results in tremendous carbon dioxide emissions. Therefore, it is vital to develop innovative strategies to reduce fossil fuel consumption by effectively utilizing the heat storage effect in packed beds. Herein, an innovative double-layered fuel segregation method with return fines embedded in the lower layer was proposed and validated, and a goal of intensively reducing fuel consumption by 16% was achieved. Specifically, the oxygen concentration in the flue gas decreased from 16.7% to 11.5%, whereas the carbon dioxide and carbon monoxide concentrations increased from 5.5% and 0.3% to 13.4% and 1.3%, respectively. Moreover, the tumbler and shatter indices increased by 1.7% and 3.2%, respectively, indicating an increase in the sinter quality. In addition to optimizing the parameters of the proposed technology, the mechanisms for intensifying fuel combustion by applying the proposed technology were elucidated. The narrow thicknesses of the combustion and over-wet zones were found to significantly contribute to the improved permeability of the sintering bed.